Gramaticalização de orações avaliativas completivas do verbo achar - Parreira, Ana Caroline de Lima [UNESP] (2014)
The proposed work addresses the non-verbal predication embedded in the verb to think aiming to discuss the status of embedded predication, from the point of view of grammaticalization (HOPPER; TRAUGOTT, 2003; LEHMANN, 1988). It is known and fairly investigated in Portuguese complex sentences composed by predicates that indicates evaluation and modality in which embed a non-verbal predication, as in I think [that your hair is beautiful]. We are interested, however, in the investigation of the complex sentence, in which an evaluative predication structured by the verb think, fits a reduced non-verbal predication without use of copular verb, as in I think [this chair to be comfortable], a complex sentence strongly integrated in syntactic, semantic and pragmatic terms when it contrasts this kind of predication to its counterparty expanded I think [that this chair is comfortable]. Through the analysis of samples of Portuguese spoken selected in Iboruna database (GONÇALVES, 2007), it was conducted an investigation of syntactic, semantic and pragmatic motivations in order to present a description of the behavior of the predicates in study. In addition, the present research, from a synchronic perspective, provides evidence for the process of grammaticalization of non-verbal predication embedded in the verb think, based on the continuum of grammaticalization and desententialization proposed by Lehmann (1988). The survey results reveal that the employment of non-verbal predicates reduced signals a speaker evaluation due to their direct experience with the source of the evaluation while expanded predication indicates an evaluation based on an experience obtained indirectly by the speaker. The comparative analysis of non-verbal predicates and developed attests that the reduced non-verbal predication are more integrated thab expanded predication, which culminated in the development of a continuum of grammaticalization from the scale proposed by ...